البناء السردي في لامية لسان الدين بن الخطيب في مدح السلطان الغني بالله - رمضان عيد محمد بدر (Maǧallaẗ Kulliyyaẗ Al-ādāb Ǧāmiʿaẗ Būrsaʿīd, 2025)
يسعى البحث إلى الوقوف على البناء السردي في لامية لسان الدين بن الخطيب في مدح السلطان الغرناطي الغني بالله، وإبراز تجليات السرد في قصيدته الشعرية، والذي حقق قدراً كبيراً من الأصالة والعمق الفني، ومدى إسهام البنية السردية في التعبير عن رؤيته ومواقفه وآرائه لواقعه المرير، وأثر عناصر هذه البنية في إبراز البناء العام للقصيدة وتقوية مستوياتها المتنوعة دلالياً وتركيبياً وإيقاعياً، وما أضافته من قيمة فنية وجمالية .    واستعان لسان الدين بن الخطيب بمكونات سردية في بنائه لقصيدته الشعرية؛ لتحقيق مصطلح "المنح الغريب في الفتح القريب" الذي اختاره عنواناً لقصيدته، ورأينا هذه المكونات السردية قائمة على الحدث وأنساقه، وعلى الشخصية التي استلهمها من الواقع المعيش وجسد من خلالها الصراع بين الأنا والآخر، وعلى الزمن الذي يعود إلى الماضي السحيق ليسترجع زمن القوة والنصر والمجد الذي كان عليه أجداد الممدوح الغرناطي الغني بالله، وعلى المكان الذي شكل فضاءاً سردياً عكس من خلاله الجو النفسي لشخصيات القصيدة المتنوعة، ومدى أثرها في رسم ملامح رؤيته الفنية .This study aims to examine the narrative structure in the Lāmiyya poem of Lisān al-Dīn Ibn al-Khaṭīb in praise of the Granadan Sultan al-Ghanī bi-Llāh. It highlights the narrative manifestations in his poetic composition, which attained a high degree of originality and artistic depth. The research also explores the extent to which the narrative structure contributes to expressing the poet’s vision, stances, and perspectives on his harsh reality, as well as the impact of its elements in reinforcing the poem’s general structure and enhancing its various semantic, syntactic, and rhythmic levels, adding artistic and aesthetic values.Ibn al-Khaṭīb employed narrative components in constructing his poem to achieve the concept of “al-minḥ al-gharīb fī al-fatḥ al-qarīb” (“The Wondrous Grant in the Imminent Triumph”), which he chose as the title for his poem. These narrative components are based on events and their sequences, characters inspired by lived reality embodying the conflict between self and other, temporal dimensions that recall a distant past to retrieve the era of strength, victory, and glory of the praised Sultan’s ancestors, and spatial dimensions that formed a narrative setting reflecting the psychological atmosphere of the poem’s diverse characters and their influence on shaping the poet’s artistic vision.